Cover of Expenditure in Milk Production at Agricultural Enterprises:the Stale and Factors of Formation - Шиян, Н. І. (Scientific Progress & Innovations, 2012)
The actuality of the problem of increasing the expenditure cover level during the process of milk production and the possible ways to solve it have been elucidated in the work. The influence level of sale price and cost priceof a production item on the level of expenditure cover at Ukrainian agricultural enterprises which produced and sold milk in 2010 has been determined by using grouping methods. The existence of a close feedback between indicators of cows productivity and the unit cost of production has been proved. Existence of dependence in 2010 between the price and cows productivity, which vary in the same direction-are increasing.